2009
DOI: 10.1007/s11096-009-9294-z
|View full text |Cite
|
Sign up to set email alerts
|

The quality of private pharmacy services in low and middle-income countries: A systematic review

Abstract: The evidence-base regarding the quality of professional services from pharmacies in low and middle income countries is limited, but indicates that standards are often deficient. If pharmacists are to contribute effectively to health care, the barriers to the provision of higher quality care and ways in which these might be overcome must be identified and examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 34 publications
7
138
0
5
Order By: Relevance
“…The provision of advice for treating the common symptoms of diarrhoea was negligible or was not in accordance with standard therapy, indicating a deficit of qualified and trained personnel at these pharmacies. The observations in our study are in line with other studies showing that the quality of professional services from pharmacies is low and the provision of advice for common symptoms in middle-income countries is limited [22]. The situation in Pakistan is not an exception and similar patterns of counselling were observed in other countries [3,[23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…The provision of advice for treating the common symptoms of diarrhoea was negligible or was not in accordance with standard therapy, indicating a deficit of qualified and trained personnel at these pharmacies. The observations in our study are in line with other studies showing that the quality of professional services from pharmacies is low and the provision of advice for common symptoms in middle-income countries is limited [22]. The situation in Pakistan is not an exception and similar patterns of counselling were observed in other countries [3,[23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…39 This is particularly the case in developing countries, including Nepal, where access to physicians is limited and prohibitively expensive for many people. 40 Curriculum reform may be required to support these new pharmaceutical care roles performed by pharmacists. The results of our study highlight areas where the pharmacy curriculum in Nepal may need to be reformed and expanded; however, further research is needed to determine whether greater coverage of the pharmacotherapy of mental disorders would translate into improved understanding of mental disorders among pharmacy students.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, educational strategies for stimulating quality improvement have been discussed, and the pharmacy sector is likely to experience regulatory changes that mandate quality improvement, public reports on the quality of individual pharmacies, and pay-for-performance systems that reward pharmacies for achieving high levels of quality [3]. In developing countries, Smith [19] conducted a systematic review and reported that the evidence-base regarding the quality of professional services from pharmacies in low and middle income countries was limited, and indicated that standards were often deficient. If pharmacists were to contribute more effectively to health care, the barriers to the provision of higher quality care and ways in which these might be overcome must be identified and examined [19].…”
Section: Discussionmentioning
confidence: 99%